Novel Anti-inflammatory Treatments in Cirrhosis. A Literature-Based Study - Kronborg, Thit Mynster; Ytting, Henriette; Hobolth, Lise; Møller, Søren; Kimer, Nina (Frontiers in Medicine, 2021)
Liver cirrhosis is a disease with multiple complications and a poor prognosis. The prevalence is increasing worldwide. Chronic inflammation is ongoing in liver cirrhosis. No cure of the inflammation is available, and current treatment of liver cirrhosis is only symptomatic. However, several different medical agents have been suggested as potential healing drugs. The majority have been tested in rodents, but few human trials are effectuated. This review focuses on medical agents described in the literature with supposed alleviating and maybe curing effects on liver cirrhosis. Twelve anti-inflammatory, five antioxidative and three drugs with effect on gut microflora and LPS pathway were found. Two drugs not categorized by the three former were found in addition. In total 42 rodent studies and seven human trials were found. Promising effects of celecoxib, aspirin, curcumin, kahweol, pentoxifylline, diosmin, statins, emricasan, and silymarin were found in cirrhotic rodent models. Few indices of effects of etanercept, glycyrrhizin arginine salt, and mitoquinone were found. Fecal microbiota transplantation is in increasing search light with a supposed potential to alleviate cirrhosis. However, human trials are in demand to verify the findings in this review.